A study of relationship between motivation and understanding toward communication in Kolej Kemahiran Tinggi Mara Ledang / Nur Ain Syuhada Mohd Salim - Mohd Salim, Nur Ain Syuhada (2015)
Many companies develop difficulties within their organization due to communication issues. Companies need to aware of potential barriers to communication. To improve the quality of communication, mangers must understand how the process of communication works. The communication process begins when an individual or group has an idea or concept and wishes to make that information known to someone else. The primary components of communication process include the sender, the channel, the message, the receiver, feedback, and noise. In KKTM Ledang, the researcher found that, some important information are not receive well either in verbal or nonverbal to among their staff. Many organisations adopted technology with gusto and equipped their employees with a range of technology to help them keep in touch. Same goes with KKTM Ledang, KKTM Ledang are using technologies as medium of communication it remains a good idea in principle, especially if it helps to reduce travelling to meetings, to the office or between offices. The technology takes over, people too often neglect to think about their audience, their message and what really needs to be said and use the functions of the technology to get them through. Staff of KKTM Ledang are rely on the technology too much. The research that researcher conduct is for to know the barriers to effective communication at KKTM Ledang. The barriers to communication may change with change in time because the needs of employees are often change with change in time. So continuous monitoring and close observation of barriers to effective communication is necessary to maintain a competent workforce. This research is important in order to understand how components of communication can be the barriers to effective communication and try to find ways to improve the communication among staff at KKTM Ledang.